Peran Dukungan Sosial dalam meningkatkan Harga Diri Ibu Primipara - Alia Rizki Fauziah; Hera Lestari Mikarsa; Wahyu Rahardjo; Tety Elida (Universitas Andalas, 2022)
Primiparous, mothers who have just had their first child experience many physical, biological ,and physiological changes, coupled with new challenges and lack of experience in parenting, make mothers tend to experience stress levels, so self-esteem is needed to optimize child care and development. One of the factors that affect self-esteem is social support, but the limited previous research related to this, this research aims to see the effect of social support on the self-esteem of primiparous mothers. A total of 250 primiparous mothers were recruited using a purposive sampling technique to fill out the self-esteem and social support scale. The results of the regression analysis showed that social support had a significant effect on self-esteem. Social support contributes 66% to the self-esteem of primiparous mothers. The most influential social support on the self-esteem of primiparous mothers is the husband's support of 35.4%. This indicates that social support, especially husband's support, is an important thing that must be considered to increase the self-esteem of primiparous mothers in adjusting to their new role as mothers. Primiparous mothers who have high self-esteem will be satisfied with their character. The existence of a positive appreciation will provide a sense of security in adjusting and reacting to stimuli from the environment